Polarization and Frequency Reconfigurable Antenna for Dual Band ISM Medical and Wi-Fi Applications - S R Murthy, K; Umakantham, K; S N Murthy, K; T P Madhav, B (International Journal of Engineering and Technology, 2018)
A hybrid reconfigurable reception apparatus is intended to work in ISM medicinal band (2.5 GHz) and Wi-Fi working groups (3.4 GHz). A winding sort of transmitting structure with absconded ground is taken in the development of the proposed recieving wire show. The planned model is furnishing recurrence reconfigurability and polarization reconfigurability with great impedance data transfer capacity and hub proportion transmission capacity. The created model estimation results are giving incredible connection reenactment results got from HFSS instrument. Explanatory examination as for the reflection coefficient, radiation design with LHCP and RHCP and hub proportion are displayed in this work.Â Â